Simple and high-yield preparation of carbon-black-supported ∼1 nm platinum nanoclusters and their oxygen reduction reactivity. Issue 35 (10th August 2021) - Kawawaki, Tokuhisa; Shimizu, Nobuyuki; Funai, Kanako; Mitomi, Yusuke; Hossain, Sakiat; Kikkawa, Soichi; Osborn, D. J.; Yamazoe, Seiji; Metha, Gregory F.; Negishi, Yuichi
Abstract : This work established a simple method for the size-selective synthesis of a series of ligand-protected platinum nanoclusters with superior oxygen reduction reactivity. Abstract : The improvement of oxygen reduction reaction (ORR) catalysts is essential before polymer electrolyte fuel cells can be used widely. To this end, we established a simple method for the size-selective synthesis of a series of ligand-protected platinum nanoclusters with ∼1 nm particle size (Pt n NCs; n = ∼35, ∼51, and ∼66) and narrow size distribution (±∼4 Pt atoms) under atmospheric conditions. Using this method, each ligand-protected ∼1 nm Pt NC was obtained in a relatively high yield (nearly 80% for Pt∼66 ). We succeeded in adsorbing each ligand-protected ∼1 nm Pt NC on carbon black (CB) and then removing most of the ligands from the surface of the Pt NCs via calcination while maintaining the original size. The obtained Pt∼35 /CB, Pt∼51 /CB, and Pt∼66 /CB exhibited ORR mass activities that were 1.6, 2.1, and 1.6 times higher, respectively, than that of commercial CB supported-Pt nanoparticles, and also display high durability.